Pengaruh Brand Credibility, Customer’s Satisfaction dan Customer’s Loyalty pada Word of Mouth di Klinik Kecantikan The-Unnathi Pakubuwono Jakarta - Abelina Dini Fitria; Innocentius Bernarto (Universitas Sam Ratulangi, 2022)
The purpose of this study is to analyze: 1) Does Brand Credibility Affect Customer’s Satisfaction positively? 2) Does Brand Credibility Affect Customer’s Loyalty positively? 3) Does Customer’s Loyalty affect Word of Mouth (WOM) positively? 5) Does Customer’s Satisfaction affect Customer’s Loyalty positively? Questionnaire was used as data collection method to all the customer’s of The Unnathi Beauty Clinic, Pakubuwono Jakarta whether they came to the retail or did home treatment within the last 3 months. They all must be older than 17 years old. Convenience sampling was used as data gathering method. Partial Lease Square-Structural Equation Modeling (PLS-SEM) analysis was done using SmartPLS 3.0. Findings of this study shows that Brand Credibility positively affect Customer’s Satisfaction and Customer’s Loyalty. Customer’s Satisfaction and Customer’s Loyalty positively affect WOM. Customer’s Satisfaction positively affect Customer’s Loyalty.